Linguistic Strategies for Building National Consciousness through Political Speeches - SOLOMON ONOVWIONA; Ojieh, Mary Enwelim-Nkem (International Journal of Language and Literary Studies, 2025)
Political office holders are one of the key actors that can help in building national consciousness among Nigerians. They can use their speeches and broadcasts to create the spirit of inclusiveness and unity, thereby providing a fertile ground for patriotism and sense of national attachment to thrive in the country. The aim of this study, therefore, was to identify the linguistic strategies used by Nigerian political leaders in their speeches to imbibe unity and patriotism among the citizens. Data were collected from six speeches delivered by three Nigerian presidents on the country’s Democracy Day and Independence Day broadcasts. The speeches were collected from the YouTube pages of Nigerian mainstream media. The audio of the speeches were transcribed into text to enable easier and deeper analysis. Qualitative analysis method was used to analyse the speeches to identify the strategic use of language in them. Two models of Halliday’s Systemic Functional Grammar provided the theoretical anchor for this analysis. One of the models, Information Structure, was used to identify the information delivered in the speeches while the second model, Register, provided the perspective for identifying the choice of words adopted in the speeches. The study discovered that the presidents delivered information that indicated the country is facing challenges, which can only be tackled if the citizens become united and work together in harmony. It also discovered that words, which show inclusiveness, endearment, and comradeship, were greatly used in the speeches. The study, therefore, concluded that Nigerian political leaders can build national consciousness if they use language judiciously to encourage unity and patriotism.